Sound perception and its effects in plants and algae. (1st December 2020) - Frongia, Francesca; Forti, Luca; Arru, Laura
ABSTRACT: Life evolved in an acoustic world. Sound is perceived in different ways by the species that inhabit the Planet. Among organisms, also some algal species seem to respond to sound stimuli with increased cell growth and productivity. The purpose of this Short Communication is to provide an overview of the current literature about various organisms and sound, with particular attention to algal organisms, which, when subjected to sound applications, can change their metabolism accordingly.